qanda-logo
search-icon
Symbol
Problem
solution-image
Concepts Illustrative Examples Transforming a quadratic function in the form $y=ax^{2}+bx+cin$ into the $fo\square D$ $y=a\left(x-h\right)^{2}+k$ $a\left(x-h\right)^{2}+kby$ completing the square. Transforming a quadratic function in the form $y=ax^{2}+bx+cin$ into the $fomn$ $y=a\left(x-h\right)^{2}+kby$ applying the formula: $h=-and$ $k=\dfrac {4ac-b^{2}} {4a}$ $h=\dfrac {-b} {2a}$ Transforming a quadratic function in the form $y=a\left(x-h\right)^{2}+k$ into the $f_{omy}=ax^{2}+bx+c$
7th-9th grade
Algebra
Search count: 126
Solution
answer-user-profile-image
Qanda teacher - manish0001
answer-reply-image
if you have any problem
feel free to ask
answer-user-profile-image
Student
thank you so much sir
Similar problem